2014
DOI: 10.1111/jop.12207
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells in the actinic cheilitis

Abstract: Therefore, our data show that Tregs accumulate in AC lesions, and these cells could be suppressing immune responses in a potentially malignant microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
3

Year Published

2016
2016
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 47 publications
2
13
0
3
Order By: Relevance
“…The immunosuppressive activity of this subpopulation of T cells may be particularly necessary in the early stages of lip carcinogenesis, in which neoplastic cells are possibly more immunogenic. As observed in this study, early-stage LLSCCs are low-grade tumors 24 demonstrated the accumulation of functional Treg cells (CD4+CD25+FoxP3+) in actinic cheilitis. Furthermore, enzyme-linked immunosorbent assays (ELISA) revealed higher expression levels of IL-10 and TGF-β and lower levels of interferon gamma (IFN-γ) in actinic cheilitis when compared to the control group (healthy gingival tissue).…”
Section: 15supporting
confidence: 74%
See 1 more Smart Citation
“…The immunosuppressive activity of this subpopulation of T cells may be particularly necessary in the early stages of lip carcinogenesis, in which neoplastic cells are possibly more immunogenic. As observed in this study, early-stage LLSCCs are low-grade tumors 24 demonstrated the accumulation of functional Treg cells (CD4+CD25+FoxP3+) in actinic cheilitis. Furthermore, enzyme-linked immunosorbent assays (ELISA) revealed higher expression levels of IL-10 and TGF-β and lower levels of interferon gamma (IFN-γ) in actinic cheilitis when compared to the control group (healthy gingival tissue).…”
Section: 15supporting
confidence: 74%
“…Furthermore, enzyme-linked immunosorbent assays (ELISA) revealed higher expression levels of IL-10 and TGF-β and lower levels of interferon gamma (IFN-γ) in actinic cheilitis when compared to the control group (healthy gingival tissue). According to Gasparoto et al, 24 the accumulation of functional Treg cells in actinic cheilitis may inhibit the proliferation of T cells and produce a microenvironment with high levels of immunosuppressive cytokines, events that contribute to the persistence, recurrence, progression, and malignant transformation of these lesions.…”
Section: 15mentioning
confidence: 99%
“…11,12 The establishment of an immunosuppressive environment could be an early event in lip carcinogenesis. In line with this suggestion, Gasparoto et al 33 demonstrated the accumulation of functional T regulatory cells (CD4+CD25+FoxP3+) in actinic cheilitis, which is characterized by potentially malignant lesions that can progress to SCCLL. These authors also observed higher expression of IL-10 and TGF-β and lower expression of IFN-γ in actinic cheilitis when compared to the control group (healthy gingival tissue).…”
Section: Discussionmentioning
confidence: 76%
“…These authors also observed higher expression of IL-10 and TGF-β and lower expression of IFN-γ in actinic cheilitis when compared to the control group (healthy gingival tissue). 33 These findings suggest the existence of a mutually reinforcing cytokine signal network between M2 TAMs and T regulatory cells in early stages of lip carcinogenesis.…”
Section: Discussionmentioning
confidence: 80%
“…Причины акти-нического хейлита -длительное и интенсивное солнеч-ное облучение в сочетании с метеорологическими факто-рами (постоянная работа на открытом воздухе, ветер, мо-роз) [12,78]. Довольно часто актинический хейлит наблю-дается у пациентов совместно с другими аллергическими состояниями типа солнечного пруриго (эритема на коже лица) [55].…”
Section: стоматология 1 2016unclassified